Preparation of DNA and RNA Fragments Containing Guanine N2‐Thioalkyl Tethers. Issue 3 (21st March 2023) - Hou, Xiaorong; Wang, Gang; Gaffney, Barbara L.; Jones, Roger A.
Abstract: This article describes procedures for preparation of deoxyguanosine and guanosine derivatives in which the guanine N 2 contains a thiopropyl tether, protected as a tert ‐butyl disulfide. After incorporation into a DNA or RNA fragment, this tether allows site‐specific cross‐linking to a thiol of a protein or another nucleic acid. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Preparation of diisopropyl‐1‐( tert ‐butylthio)‐1, 2‐hydrazinedicarboxylate (4 ) Basic Protocol 2 : Preparation of the 2′‐deoxyguanosine N 2 ‐propyl‐ tert ‐butyl disulfide phosphoramidite (12 ) Basic Protocol 3 : Preparation of the guanosine N 2 ‐propyl‐ tert ‐butyl disulfide phosphoramidite (20 ) Basic Protocol 4 : Preparation of DNA fragments containing N 2 ‐propyl‐ tert ‐butyl disulfide guanine Alternate Protocol : Preparation of RNA fragments containing N 2 ‐propyl‐ tert ‐butyl disulfide guanine Basic Protocol 5 : Conversion of N 2 ‐propyl‐ tert ‐butyl disulfide to the free thiol, disulfide 5‐thio‐2‐nitrobenzoic acid disulfide, or ethylamine disulfide